Analysis of Relation between Parity and Exclusive Breastfeeding in Indonesia Based on Indonesia Demographic and Health Surveys 2017 - Imro’atul Khasanah; Mahendra Tri Arif Sampurna; Astika Gita Ningrum; Dewi Setyowati; Hodimatum Mahiroh; Hiromi Ogasawara (STRADA : Jurnal Ilmiah Kesehatan, 2022)
Exclusive breastfeeding is the provision of mother’ milk from birth until six months of age without giving or replacing it with other food or drinks except for the provision of drugs, vitamins, and minerals. In 2019 national coverage of exclusive breastfeeding for infants in Indonesia was 67.74%. Various efforts have been made by the government to increase the coverage of exclusive breastfeeding, including: government regulations with the implementation if advocacy and supervision regarding exclusive breastfeeding which are the duties and responsibilities of the central and local governments. The purpose is to analyze the relation between parity and exclusive breastfeeding in Indonesia based on the Indonesia Demographic and Health Surveys (IDHS) 2017. The research is quantitative and it is an analytical research. The research design used cross sectional study. The samples were 2.301 respondents after cleaning and weighted data. The independent variables in this study is parity.